Practice motivation and life satisfaction of athletes of team sports: Comparative study between adapted and regular sport - Batista, Marco (2019)
Introduction: Sports practice provides not only physical but also psychological and social benefits. Objective: The subject of Adapted Sport is still very scarce and according to that in this study we evaluated and compared Self-Determined Motivation, Basic Psychological Needs, Life Satisfaction and Affects among Athletes of Adapted Sport and Regular Sport, in Handball and Basketball. Methodology: A total of 183 athletes (N = 183) participated in which 80 were athletes of adapted sports and the remaining 103 were regular athletes, aged between 16 and 69. We used four questionnaires that evaluate the variables described: Behavioral Regulation in Sport Questionnaire (BRSQ), Basic Psychological Needs Exercise Scale (BPNES), Life Satisfaction Scale (SWLS) and Positive and Negative Affects Schedule (PANAS). Results: Our results were positive that sports practice has a significant positive effect on life satisfaction in regular athletes, who have more hours of weekly practice than athletes in adapted sports. We have proved the Auto-determination Theory, with the positive correlation obtained in the adapted sport athlete’s, between the autonomous motivation and the basic psychological needs, as well as the life satisfaction and the positive affections. We observed that basic psychological needs and positive affects were good predictors of life satisfaction in athletes of adapted sport. In terms of size effect magnitude of adapted sport practice, the number of years of practice showed a reduced to moderate effect in the variables under analysis.